Cross‐elicitation responses to 2‐methoxymethyl‐p‐phenylenediamine in p‐phenylenediamine‐allergic individuals: Results from open use testing and diagnostic patch testing. (7th August 2018) - Schuttelaar, Marie L.; Dittmar, Daan; Burgerhof, Johannes G. M.; Blömeke, Brunhilde; Goebel, Carsten
Abstract : Background: Allergic contact dermatitis caused by p ‐phenylenediamine (PPD) is a health concern for hair dye users. Because of its lower sensitization potency, the PPD derivative 2‐methoxymethyl‐ p ‐phenylenediamine (ME‐PPD) has been developed as an alternative hair dye for primary prevention. However, cross‐elicitation responses can occur in PPD‐allergic subjects. Objectives: To compare cross‐elicitation responses to ME‐PPD in open use and diagnostic patch testing of PPD‐allergic subjects with hair dye‐related allergic contact dermatitis. Methods: Reactions to ME‐PPD were investigated in 25 PPD‐allergic subjects by performing (1) 45‐minute open use testing with a hair dye containing 2.0% of either ME‐PPD or PPD, and (2) patch testing with increasing ME‐PPD concentrations (0.1%–2.0% pet.). Results: Of the 25 PPD‐allergic subjects, 21 (84%) reacted to open use testing with a hair dye containing 2.0% PPD, and testing with 2.0% ME‐PPD led to cross‐elicitation in 12 (48%). When patch tested with increasing ME‐PPD concentrations, 13 (52%) cross‐reacted at 0.1% (lowest dose) and 21 (84%) at 2.0% (highest dose), indicating decreased reactivity as compared with published PPD dose‐response data. Conclusion: In line with the decreased cross‐reactivity of ME‐PPD in hair dye open use testing, PPD‐allergic subjects show an attenuated cross‐elicitation dose response to ME‐PPD in patch testing.